1998
DOI: 10.1210/en.139.2.520
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Kinase Activity of the Insulin Receptor Account for an Increased Insulin Sensitivity of Mammary Gland in Late Pregnancy

Abstract: Mammary gland is an organ that undergoes cycles of growth, differentiation, and function during pregnancy and lactation. Although it is known that the gland enhances its sensitivity to insulin during lactation, it remains to be investigated whether this increased sensitivity develops during pregnancy and which are the molecular mechanisms underlying such a change. To address this issue, virgin and late-pregnant rats were subjected to a continuous infusion with 50% glucose for 72 h to produce a prolonged hyperi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 27 publications
2
9
0
Order By: Relevance
“…1A). These data fit well with the observation that the amount of IR protein does not change in the skeletal muscle of pregnant women (30) and support the hypothesis that, similar to other situations of insulin resistance like obesity or type 2 diabetes (24), postbinding receptor defects play a major role on development of peripheral insulin resistance at late pregnancy.…”
Section: Insulin-stimulated Tyrosine Phosphorylation Of Ir and Irs-1 supporting
confidence: 88%
“…1A). These data fit well with the observation that the amount of IR protein does not change in the skeletal muscle of pregnant women (30) and support the hypothesis that, similar to other situations of insulin resistance like obesity or type 2 diabetes (24), postbinding receptor defects play a major role on development of peripheral insulin resistance at late pregnancy.…”
Section: Insulin-stimulated Tyrosine Phosphorylation Of Ir and Irs-1 supporting
confidence: 88%
“…Different from the insulin-resistant condition that is normally present during late pregnancy in adipose tissue (54,55) and skeletal muscle (55)(56)(57), the mammary gland shows increased insulin sensitivity caused by an augmented kinase activity of the insulin receptor (42). It has also been shown that insulin participates in the enhanced expression of LPL in the mammary gland during late pregnancy (58), whereas it is responsible for the decrease of LPL activity normally seen in maternal white adipose tissue (59,60).…”
Section: Discussionmentioning
confidence: 94%
“…To attain a better understanding of the potential function of HSL in the mammary gland, the present work was addressed at determining the cell types that might express this protein and the changes that take place in its expression and activity in the mammary gland during pregnancy and lactation in the rat. In addition, because insulin is well known as the most active antilipolytic hormone (39,40) and during late pregnancy and lactation the mammary gland remains highly sensitive to it (41,42), the study was extended to determine the potential relationship between plasma insulin levels and mammary gland HSL activity during those same stages.…”
mentioning
confidence: 99%
“…Since insulin has been shown to decrease β 3 -AR levels (Engfeldt et al 1988;Feve et al 1994;Hadri et al 1997), the decrease observed in this adrenoceptor, mainly in late pregnancy, might be explained by both hyperinsulinaemia and enhanced insulin sensitivity in the mammary gland in late-pregnant rats (Carrascosa et al 1998), contrary to the insulin resistance present in most tissues. During late pregnancy, the lower specific content of the rate-limiting enzyme of lipolysis, HSL, also points to decreased lipolytic activity in this tissue, which might contribute to its increased lipid storage.…”
Section: Discussionmentioning
confidence: 99%